Firm Value in The Financial Sector: Enterprise Risk Management, Islamic Social Reporting, and Profitability Disclosure - Hartomi Maulana; Mutia Asmarani; Rahma Yudi Astuti; Ely Windarti Hastuti; Soritua Ahmad Ramdani Harahap (AFRE (Accounting and Financial Review), 2024)
This study aims to analyse the effect of disclosure of ERM, ISR and Profitability on the value of financial sector companies listed on the Sharia Securities List for four periods (2018-2021). The data obtained by researchers were 4 financial sector companies listed on the Sharia Securities List for four periods (2018-2021). The method used in this research is descriptive quantitative, with panel data regression analysis in the data analysis. The results found in this study are, there is no relationship between ERM and the value of financial sector companies. Then there is a negative relationship between ISR and firm value. However, in Profitability and the value of financial sector companies there is a significant positive influence. Likewise, the results of the simultaneous significane test conducted on firm value have a significant positive effect.DOI: https://doi.org/10.26905/afr.v7i2.11418